Representation of Intimate Partner Violence Against Women in Swedish News Media: A Discourse Analysis - Karlsson, Nadja (Violence against women, 2021)
Despite being rated as some of the world’s most gender equal countries, Sweden and neighboring Nordic nations show high rates of intimate partner violence against women (IPVAW). As the news media contribute to the shaping of public attitudes, this article pursues a two-step discourse analysis of how IPVAW was represented in seven Swedish newspapers during 2018. Although an individualistic discourse on IPVAW was found to be most prevalent, articles where perpetrators were presented as non-Swedish more frequently contained a structural framing of IPVAW. This confirms previously noted tendencies toward individualization and othering of IPVAW in Sweden.